2022
DOI: 10.2147/rmhp.s394035
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Delivery of Enteral Nutrition in Intensive Care Settings in Saudi Arabia: A Comparative Study of the Perceptions of Health Care Providers Working in Adult and Paediatric ICUs

Abstract: Background and Aims: Achieving optimal nutrition prescription is challenging in critically ill patients. Many factors can hinder the adequate delivery of enteral nutrition (EN) in intensive care units (ICUs). In this study, we aim to describe EN barriers and compare the perceptions of health care practitioners working in adult and paediatric ICUs regarding these barriers. Methods: In this cross-sectional study, data were collected via online survey. All physicians, dietitians, and nurses working in adult or pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…This results in substandard feeding (Brierley-Hobson et al, 2019 ; Lee et al, 2018 ). Additionally, various issues related to enteral nutrition, such as abdominal distension, diarrhea, and aspiration, may arise, impacting the progress of enteral nutrition in children (Zaher, 2022 ; Zhang et al, 2021 ). Some studies (Chen et al, 2022 ; Feiyue et al, 2023 ) have indicated that substandard feeding through early enteral nutrition in critically ill patients can prolong their ICU stay and increase medical expenses.…”
Section: Introductionmentioning
confidence: 99%
“…This results in substandard feeding (Brierley-Hobson et al, 2019 ; Lee et al, 2018 ). Additionally, various issues related to enteral nutrition, such as abdominal distension, diarrhea, and aspiration, may arise, impacting the progress of enteral nutrition in children (Zaher, 2022 ; Zhang et al, 2021 ). Some studies (Chen et al, 2022 ; Feiyue et al, 2023 ) have indicated that substandard feeding through early enteral nutrition in critically ill patients can prolong their ICU stay and increase medical expenses.…”
Section: Introductionmentioning
confidence: 99%